Religious and spiritual coping of the loss of a loved one - Yoffe, Laura (2015)
This article analyses religious and spiritual coping of negative and stressful events such as the loss of a loved one. The study case of a religious catholic woman who lost a loved one is part of my Docthoral Thesis (an exploratory and descriptive study done with religious persons of different creeds), where it was verified that prayers, meditation, spiritual healing, funerary rituals and social support promote positive effects and physical, psychological, mental and spiritual well- being of religious people who mourn the loss of a loved one.